Challenges to community arts and online communication during Ireland’s Covid-19 lockdowns - Crowley, Kathryn (Culture Caleidoscoop, 2023)
This paper is an auto-ethnographic account of an online project that I instigated in Ireland during the Covid-19 pandemic. It reflects on the difficulties in building a group project with people who had never met before, the move to online events, my lack of skills and experience in that realm, and unexpected communication that was unsettling, all of which were exacerbated by my personal struggles during a global pandemic.